Automated Device for Welding the Window of the Car Window Heating System (Texas Journal of Engineering and Technology, 2022)
The article presents a design for soldering the terminal of the autoglass heating system in a semi-automatic mode, intended for manufacturers of automotive glass. The possibilities of the proposed design, the differences from existing designs, and the method of use are described. An algorithm for the operation of a semi-automatic structure is presented.